Jhejhel Tradition as a Concept of UCE Implementation on Improving The Economy of The Kangean Island Community in The Pandemic - Muta’allim; Tabroni, Imam; Mahidin, La; Sulalah, Asia Anis; Ghaffar, Abdul Azizul (Proceedings of Annual Conference on Community Engagement, 2022)
The COVID-19 pandemic has succeeded in robbing human activities of socio-religious, educational, economic and other activities. In this case, the COVID-19 pandemic was very successful in snatching the community’s economy, so this had a very bad impact on the progress of education, welfare, and the economy. Therefore, the author presents the concept of implementing UCE in improving the economy of the Kangean Islands community during the Pandemic. This study aims to identify and describe the concept of implementing UCE in improving the economy of the Kangean Islands community through the Jhejhel tradition. This research is a type of qualitative descriptive research. The method used in this research is the method of observation and interviews which are equipped with documentation techniques. The results show that (1) the concept of implementing UCE can improve the economy of the Kangean community; (2) Jhejhel is an alternative solution in strengthening the economy of the Kangean community during the Pandemic; (3) the concept of implementing UCE greatly influences the increase in the selling price of buffalo in the Kangean Islands; and (4) the concept of successful implementation of UCE in eradicating poverty through the Jhejhel in the Kangean islands.